The Influence of Work Commitment and Work Discipline on Employee Job Satisfaction and Performance of Bombana Regency Inspectorate Employees - Mufassir Mufassir; Abd Azis Muthalib; Muh Nur; Rince Tambunan (Syntax Idea)
The aim of this research is to determine and analyze: (1) The influence of work commitment on the performance of Bombana Regency Inspectorate employees; (2) The influence of work commitment on the performance of Bombana Regency Inspectorate employees; (3) The influence of work discipline on job satisfaction of Bombana Regency Inspectorate employees; (4) The influence of work discipline on the performance of Bombana Regency Inspectorate employees; (5) The influence of job satisfaction on the performance of Bombana Regency Inspectorate employees. The population in this study were all 49 Bombana Regency Inspectorate employees with ASN status and were also used as respondents in this study using census techniques. The data analysis method used in this research is descriptive analysis and inferential statistics, namely Partial Least Square (PLS). The research results state that: (1) Work commitment has a positive and significant effect on job satisfaction of Bombana Regency Inspectorate employees; (2) Work commitment has a positive and significant effect on the performance of Bombana Regency Inspectorate employees; (3) Work discipline has a positive and significant effect on job satisfaction of Bombana Regency Inspectorate employees; (4) Work discipline has a positive and significant effect on the performance of Bombana Regency Inspectorate employees; (5) Employee job satisfaction has a positive and significant effect on the performance of Bombana Regency Inspectorate employees